Blood coagulation dynamics in haemostasis - Mann, K. G.; Orfeo, T.; Butenas, S.; Undas, A.; Brummel-Ziedins, K. (Hämostaseologie, 2009)
Our studies involve computational simulations, a reconstructed plasma/platelet proteome, whole blood in vitro and blood exuding from microvascular wounds. All studies indicate that in normal haemostasis, the binding of tissue factor (TF) with plasma factor (F) VIIa (extrinsic FXase complex) results in the initiation phase of the procoagulant response. This phase is negatively regulated by tissue factor pathway inhibitor (TFPI) in combination with antithrombin (AT) and the protein C (PC) pathway. The synergy between these inhibitors provides a threshold-limited reaction in which a stimulus of sufficient magnitude must be provided for continuation of the reaction. With sufficient stimulus, the FXa produced activates some prothrombin. This initial thrombin activates the procofactors and platelets required for presentation of the intrinsic FXase (FVIIIa- FIXa) and prothrombinase (FVa-FXa) complexes which drive the subsequent propagation phase; continuous downregulation of which is provided by AT and the thrombinthrombomodulin- PC complex. FXa generation during the propagation phase is largely (>90%) provided by the intrinsic FXase complex. TF is required for the initiation phase of the reaction but becomes non-essential once the propagation phase has been achieved. The propagation phase catalysts (FVIIIa-FIXa and FVa-FXa) continue to drive the reaction as blood is resupplied to the wound site by flow. Ultimately, the control of the reaction is governed by the pro- and anticoagulant dynamics and the supply of blood reactants to the site of a perforating injury. Our systems have been utilized to examine the qualities of hypothetical and novel antihaemorrhagic and anticoagulation agents and in epidemiologic studies of venous and arterial thrombosis and haemorrhagic pathology.
Keywords: Thrombin; blood coagulation; haemostasis; numerical models; phenotype variability